474 Repositioning monensin: Enhancing anti-cancer activity and immune modulation in breast cancer cells - Alicja Urbaniak; Eric Siegel; Marta Jędrzejczyk; Greta Klejborowska; Natalia Stępczyńska; Adam Huczyński; Bolni Marius Nagalo; Amit K. Tiwari; Eric U. Yee; Thomas Kelly; Steven Post; Alan J. Tackett (Journal of Clinical and Translational Science)
Objectives/Goals: Monensin is FDA approved for use in veterinary medicine. Recent studies pointed to its potent anticancer activity. Since de novo drug discovery process typically takes 10 to 15 years and requires an investment of approximately $1.3 to $3 billion, drug repositioning can bypass several steps in this process and increase the potential for success. Methods/Study Population: Cell viability assays were conducted on human MDA-MB-231, MDA-MB-468, and MCF10A breast cancer cell lines and mouse EO771 and 4T1 breast cancer cell lines. MDA-MB-231 cell line was used in all the studies unless specified otherwise. Time course levels of Bcl-2, Bak, p62, and LC3II were assessed via Western blotting with GAPDH as a loading control. Proteomics analysis was conducted by the IDEA National Resource for Quantitative Proteomics. Time course levels of major histocompatibility complex (MHC) I and II and calreticulin were evaluated using flow cytometry. At least three biological replicates have been conducted for each experiment. Results/Anticipated Results: Monensin and several of its novel analogs were potent toward human and mouse breast cancer cell lines. Furthermore, they induced apoptotic cell death as evidenced by Annexin V/PI assay, downregulation of Bcl-2, and upregulation of Bak in MDA-MB-231 cells. Proteomics analysis revealed that several molecular pathways related to MHC class I and II antigen presentation were significantly altered following treatment with these compounds. Additionally, monensin and its analogs significantly increased the expression of MHC class I and II. Our studies also showed that monensin and its analogs increase the surface calreticulin levels. Treatment of MDA-MB-231 cells with these compounds also resulted in an increase in p62 and LC3II expression, suggesting a disruption of the autophagic process. Discussion/Significance of Impact: These results suggest that monensin and its analogs not only exhibit anti-breast cancer cell activity but also modulate immune-related pathways. By disrupting autophagy and enhancing calreticulin levels, these compounds may potentiate antitumor immune responses, providing a promising avenue for drug repositioning in cancer therapy.